2010
DOI: 10.1016/j.ygyno.2009.09.027
|View full text |Cite
|
Sign up to set email alerts
|

Serum low-density lipoprotein levels correlate with survival in advanced stage epithelial ovarian cancers

Abstract: Objective Recent data suggest patients with epithelial ovarian cancers on statin therapy have improved survival. We have hypothesized that statins influence ovarian cancer outcome through alteration of lipoprotein profiles, and sought to determine correlations between lipoprotein levels and survival in women with advanced stage disease. Methods After IRB approval, we identified patients with stage IIIC/IV epithelial ovarian cancer with banked prediagnostic fasting serum. Serum was assayed for levels of total… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
35
1

Year Published

2010
2010
2021
2021

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 47 publications
(41 citation statements)
references
References 14 publications
(13 reference statements)
5
35
1
Order By: Relevance
“…Li et al 33 reported elevated tg levels (32%) in ovarian cancer patients, but previously, Ostroumova et al 34 reported lower tg levels.…”
Section: Dietary Lipids and Their Metabolism In Ovarian Cancermentioning
confidence: 89%
“…Li et al 33 reported elevated tg levels (32%) in ovarian cancer patients, but previously, Ostroumova et al 34 reported lower tg levels.…”
Section: Dietary Lipids and Their Metabolism In Ovarian Cancermentioning
confidence: 89%
“…Effect of statin and aspirin use on development of deep vein thrombosis, as a contributor to mortality, has failed to show a decreased risk of thromboembolic events, so it is unlikely that the survival benefit is related to prevention of thrombosis. 23 Li et al 24 have reported that decreased LDL was associated with survival in advanced-stage epithelial ovarian cancers of predominately papillary serous histologic types. These data suggest biological plausibility for a mechanism related to lipid metabolism as an explanation of the effect of statin therapy on mortality from cancer.…”
Section: Discussionmentioning
confidence: 99%
“…The Health Professionals Followup Study identified statin users to have a significantly lower risk of metastatic and fatal disease in prostate cancer patients (33). In women with advanced-stage epithelial ovarian cancers, a statistically significant longer time to progression and improved overall survival was observed for those patients also on statin therapy (34) and, more recently, LDL was demonstrated to be a significant predictor of clinical outcome in advanced epithelial ovarian cancer patients (35). In another study, paraoxonase activity (a key anti-oxidant protein associated with HDL) correlated inversely with stage, grade, and CA-125 level of ovarian cancer (36).…”
Section: Apoa-i Mimetic Peptides Inhibit Viability Of Human Ovarian Cmentioning
confidence: 99%